Association of built environment with walking distance to public transit stops in Hanoi - Chu, Anh Tuấn (2020)
Similar to many other developing cities, Hanoi, the capital city of Vietnam, has also faced many serious problems caused by spontaneous urban development and massive private vehicles. As a part of solutions, public transportation systems in Hanoi were paid attention to be invested and developed. However, Public transportation meets only partially the travelling demand of urban people. Even recent years, the productivity of buses in Hanoi tends to be restrain and even going down in some years. Therefore, how to encourage and attract people to use public transportation modes is a more and more urgent topic. This research focuses on a key factor which greatly influences the use of transit services. This is Walking distance to transit stop and impacts of built environment on this walking distance of riders. A Poison Regression model is estimated to analyze the associations of built environment and walking distance to public transit stop using a dataset collected from a questionnaire-based Onboard survey in May 2019 with the geospatial data of BE variables where the dataset contains 609 respondents of the Hanoi Metropolitan Area. The results unveiled that: (1) Walking is the majority mode of both bus trips from home to transit stop and from transit stop to final destination; (2) The assumptions about walking distance to public stops (threshold of 400 meters) that planners have given are consistent with the Hanoi context; (3) BE variables may have both positive/negative impacts on walking distance to public transit stops. Finally, some policy recommendations were produced to support for the use of the public transportation modes in Hanoi.